2017
DOI: 10.1021/acscatal.7b03571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Side-Chain Structure of Perfluoro-Sulfonic Acid Ionomers on the Oxygen Reduction Reaction on the Surface of Pt

Abstract: The effect of side-chain structures in perfluoro-sulfonic acid ionomers on the adsorption of the terminal sulfonate moiety on the surface of Pt is investigated with voltammetry and surface-enhanced infrared absorption spectroscopy (SEIRAS). Analyses with lowmolecular-weight model anions with and without an ether group in the perfluoro-alkyl chain indicate that the anions are adsorbed on Pt through one or two oxygen atom(s) of the terminal sulfonate group and that the oxygen atom of the ether group also interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(149 citation statements)
references
References 42 publications
(71 reference statements)
5
137
1
Order By: Relevance
“…A recent vibrational spectroscopy study showed that the sulfonic groups of Nafion coordinate with Pt . A more recent study has found evidence of ether groups in the Nafion side chain to interact with Pt surface as well . However, these studies do not provide evidence of whether or why Nafion densification on Pt would occur.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent vibrational spectroscopy study showed that the sulfonic groups of Nafion coordinate with Pt . A more recent study has found evidence of ether groups in the Nafion side chain to interact with Pt surface as well . However, these studies do not provide evidence of whether or why Nafion densification on Pt would occur.…”
Section: Discussionmentioning
confidence: 96%
“…From this, it was inferred that Au and Pt surfaces have a lower affinity to the sulfonic acid/water phase than to the more hydrophilic SiO 2 surface. However, from spectroelectrochemical measurements, it is known that Pt surfaces have strong affinity for sulfonic group, resulting in poisoning of the Pt catalyst in fuel cells . In another NR study, interfacial structure in hydrated Nafion on Pt, PtO, and glassy carbon substrates was observed .…”
Section: Discussionmentioning
confidence: 99%
“…207,208 Perfluorosulfonic acids (PFSA) such as Nafion used for polymer electrolytes also specifically adsorb on the Pt(111) surface and decrease the ORR activity. [209][210][211] The IRAS and SEIRAS measurements suggested that the sulfonate group in PFSA adsorbs on Pt via one or two oxygen atoms, and the ether group also interacts with the surface. 211,212 The adsorbed species formed during the surface oxidation such as OH ad is a key factor in the ORR activity as well as the specifically-adsorbed electrolyte species.…”
Section: Operando Surface-electrochemical Spectrometry For Oxygen Redmentioning
confidence: 99%
“…[209][210][211] The IRAS and SEIRAS measurements suggested that the sulfonate group in PFSA adsorbs on Pt via one or two oxygen atoms, and the ether group also interacts with the surface. 211,212 The adsorbed species formed during the surface oxidation such as OH ad is a key factor in the ORR activity as well as the specifically-adsorbed electrolyte species. The equation of OH ad formation is as follows:…”
Section: Operando Surface-electrochemical Spectrometry For Oxygen Redmentioning
confidence: 99%
“…Pt catalysts not in direct contact with ionomer (see Figure 1 a) may not be accessible to protons under low relative humidity (RH) conditions. Recently, it has been identified that the chemical structure of ionomer dictates the chemical environment of the electrochemically active interface including poisoning by sulfonic group and ultimately affecting the oxygen reduction reaction (ORR) activity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%